MENEMUKAN MUATAN PASTORAL CARE DALAM KEARIFAN LOKAL MĔDĔDAL᷊INGGĔHO: Sebuah Analisis Konseling Pastoral Berbasis Budaya - Yohan Brek; Rustam Effendi Antara (Institut Agama Kristen Negeri Manado, 2022)
The church is in the midst of changing times. In that position the church must not lose its role as aguide for the people. The role of guiding the people is a pastoral role called pastoral counseling. To answer tha, the church’s creativity is needed in terms of carrying out pastoral counseling. One of them is by exploring the richness of lokal wisdom where the church serves. The Mĕdĕdal᷊inggĕho model is one of them because in this local wisdom the content of pastoral care values is presented which is relevant to the context of this dynamic church service such as the basis of is implementation is love and concern for others displays the function of pastoral counseling and empowers church members to become counselors for others by penetrating difference boundaries